A single-frequency laser on the base of Er – Yb co-doped optical fiber with fiber Bragg gratings - Alrumeithi, Juma; Goncharenko, Igor A. (Journal of the Belarusian State University. Physics, 2023)
The structure of the compact narrow-band fiber lasers operating in a single longitudinal mode (single-frequency lasers) has been considered. The single-frequency fiber lasers are widely used in WDM telecommunication systems, highresolution sensors, spectrometers, as well as for lightimaging detection, detection of gravitational waves and creation of multikilowatt laser systems based on coherent combining of laser beams. The proposed laser is based on the short length of optical fiber co-doped with Er3+ and Yb3+ ions. For cavity feedback a Fabry – Perot resonator is formed by using fiber Bragg gratings written on the ends of the doped fiber section. On the base of the numerical simulations the optimisation of the laser elements parameters has been carried out in order to achieve the single longitudinal mode laser generation at 1550 nm wavelength that corresponds to the minimum loss generated by the telecommunication fibers. The theoretical model is based on the steady state solutions of the rate equations resulting from the optical fields and ions interaction inside the Er3+ – Yb3+ co-doped silica fiber. The mathematical equations are solved using an iterative method by Matlab to provide an analysis of the energy levels of erbium and ytterbium ions doping the silica fiber. For the calculation of the fiber Bragg grating reflectivity the original algorithm based on the method of lines has been applied. A series of simulations have been performed by using the Optisystem software to obtain the modelling of the dynamic behaviour of the proposed Er3+ – Yb3+ co-doped fiber laser. The optimised Er3+ – Yb3+ co-doped fiber laser demonstrated a continuous wave power of 0.67 W at 1550 nm wavelength for a pump power of 1 W with a slope efficiency of 67 %.